Predictors of mortality for people aged over 65 years receiving mental health care for delirium in a South London Mental Health Trust, UK: a retrospective survival analysis. (14th October 2014) - Ward, Geoff; Perera, Gayan; Stewart, Robert
<x xml:space="preserve">Abstract</x> Background Delirium is a common phenomenon in older people. Using a large mental health care data resource, we investigated mortality rates and predictors of mortality following delirium in older people. Methods The South London and Maudsley NHS Foundation Trust (SLAM) Clinical Record Interactive Search (CRIS) was used to retrieve anonymised data on patients known to mental health services who were over 65 years of age and received a diagnosis of delirium during a 3‐year period. Age‐standardised and gender‐standardised mortality rates (SMRs) were calculated, and predictors of survival were investigated considering demographic factors, health status rated on the Health of the National Outcome Scale (HoNOS), cognitive function and previous or contemporaneous diagnosed dementia. Results In 974 patients with delirium, 1‐ and 3‐year mortality rates were 37.2 and 54.9% respectively, representing an SMR of 4.7 overall (95% CI: 4.3–5.1). SMR was 5.2 (95% CI: 4.6–5.7) for patients with delirium without prior dementia; SMR was 4.1 (95% CI: 3.6–4.7) for patients with dementia preceding delirium and 2.2 (2.0–2.5) excluding deaths within 6 months of the delirium diagnosis. Significant predictors of mortality in fully adjusted models were older age, male gender, white (compared with non‐white) ethnicity, and HoNOS subscales measuring physical ill‐health and functional impairment. No mortality associations were found with cognitive function, dementia, or psychological symptoms. Conclusions In people with delirium diagnosed by mental health services, mortality risk was high and predicted by demographic and physical health status rather than by cognitive function or psychological profile. © 2014 The Authors. International Journal of Geriatric Psychiatry published by John Wiley & Sons, Ltd.